PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI KANTOR CAMAT KUPITAN KABUPATEN SIJUNJUNG - F. Yasmeardi; Emilza Putri (Jurnal Public Administration, Business and Rural Development Planning, 2019)
Work discipline is one of the factors that can affect employee performance. Work discipline is an obedient and obedient attitude to rules based on personal awareness without any coercion from outside. This kind of attitude is not only demanded from an employee as an individual but also a group of people who are members of an organization. With discipline employees will be more responsible for their duties so that organizational goals can be realized. The work discipline of employees at the Kupitan Sub-district Office of Sijunjung Regency is still not optimal, this can be seen from the high level of employee absenteeism, lack of accuracy in working so that there is often a waste of labor and money, lack of employee obedience in following standards and regulations at work, such as when working hours are ongoing, employees are often outside the room or office rather than doing their duties and responsibilities / functions because they are ignored, there are still employees who often do other activities outside the office's interests